DNA Damage in Peripheral Blood Mononuclear Cells and Neutrophils of Dairy Cows during the Transition Period: Experimental Investigation - Tharwat , Mohamed; Oikawa , Shin (Advanced Research in Biological Science Vol. 5, 2023)
The purpose of this study was to look at the apoptotic process in peripheral blood mononuclear cells (PBMC) and polymorphonuclear neutrophil leukocytes (PMN) in dairy cattle during the transition period. This period is characterized by marked changes in the endocrine status of the animals that are much more dramatic than at any other time in the lactation gestation cycle, and by a reduction in feed intake when nutrient demand for the developing conceptus and the impending lactogenesis are increasing. Blood samples were taken from four dairy cows three weeks before projected parturition (wk -3), during parturition (ww 0), and three weeks after parturition (wk +3). The comet test was used to assess the DNA damage of PBMC and PMN using visual scoring (arbitrary units). Undamaged DNA remained in the core (score 0), while broken DNA traveled from the core to the anode, generating a comet tail (scoring 1-4). Significantly higher scores in PBMC were reported at wk 0 and wk +3 compared to PMN, despite no significant changes in scores in either cell type across the study period. It has been suggested that the apoptotic rate of PBMC is faster than that of PMC during the transition period.